Children, youth and development - Ansell, Nicola (London Routledge, Taylor & Francis Group, 2017)
Acknowledgements -- List of abbreviations -- Introduction -- Globalising models of childhood and youth -- Experiencing global processes : poverty and inequality; development and globalisation -- Immediate contexts: growing up with families and peers in a changing world -- Protecting children? addressing violence, exploitation and abuse -- The politics of young people : rights, participation, activism -- Health: ensuring survival and wellbeing? -- Education : encounters with schooling -- Work : exploiting children, empowering youth? -- Changing environments: threats and opportunities -- Migration: young people on the move -- Postscript.
Includes bibliographical references and index.
Keywords: Children--Social conditions